Accent bias and equity: implications for healthcare - Roth, Evelyn N. (Frontiers in Communication, 2025)
Healthcare delivery, particularly as it is provided through telephone triage presents unique challenges for research since it sits at the intersection of different disciplines with different research traditions and represents a safety critical domain. Sociolinguistics provides health communication with valuable insights, highlighting how language attitudes and biases, particularly towards non-standard or accented speech, affect judgments on credibility, intelligence, and likability. This is critical in medical contexts where, e.g., pain is self-reported verbally and underlying biases may influence care decisions. Unlike in-person consultations, telephone triage lacks visual and physical examination cues, relying heavily on acoustic information, which may amplify language-based biases. Researching language bias in healthcare is challenging, but sociolinguistic methods offer neutral research pathways to improve delivery. This mini-review explores the influence of language biases on health communication and patient care, outlines methodological approaches, and suggests interventions for addressing unconscious biases, with implications extending to healthcare equity and linguistic competence in medical education.